Effects of exercise intensity and duration on lipid metabolism in trained men - Toyooka, J.; Matsuo, K. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this study was to identify the point (% Vo2 max) of maximal rate of fat oxidation and the changes in lipid metabolism during 2-hour treadmill exercise at intensities of 30, 50 and 70 %Vo2 max. Summary: It was suggested that the fat oxidation was most enhanced at 70 %Vo2 max. Also, it was observed that lipid metabolism was accelerated further when exercise was longer than 90 minutes at all intensities. The finding that a relatively heavy exercise intensity elicits maximal fat oxidation in nine trained men has application in exercise prescription, as it refutes the belief that low -intensity exercise is best for fat loss.